Design of Digital Interaction for Complex Museum Collections - Laura Loredana Micoli; Giandomenico Caruso; Gabriele Guidi (Multimodal Technologies and Interaction, 2020)
Interactive multimedia applications in museums generally aim at integrating into the exhibition complementary information delivered through engaging narratives. This article discusses a possible approach for effectively designing an interactive app for museum collections whose physical pieces are mutually related by multiple and articulated logical interconnections referring to elements of immaterial cultural heritage that would not be easy to bring to the public with traditional means. As proof of this concept, a specific case related to ancient Egyptian civilization has been developed. A collection of Egyptian artifacts such as mummies, coffins, and amulets, associated with symbols, divinities, and magic spells through the structured funerary ritual typical of that civilization, has been explained through a virtual application based on the concepts discussed in the methodological section.